At any cost: a paradigm shift in the culture of caesarean section rate monitoring in the United Kingdom - Oguljemal Redjepova; Ashwini Bilagi (Journal of Obstetrics and Gynaecology)
Recent reviews into maternity safety in the United Kingdom (UK) have led to a paradigm shift in culture and policy around caesarean section (CS) rate monitoring. CS rates in the UK have risen considerably over the last few decades and, in this time, there has been national effort at the level of government to kerb such rises due to concerns about the associated morbidity, and the medicalisation of birth. However, recent findings from two landmark reviews raise concerns that the pursuit of low CS rates may have caused harm to patients in some instances, and this has led the UK government to recommend cessation of the use of total CS rates as performance metric for maternity services. Instead, it is proposed that such data be collected with use of the Robson classification. Ongoing appraisal of maternity safety will be required to evaluate the effect of these changes in future.